Assessing The Effectiveness of Sharia-Based SustainabilityReporting Model in Enhancing Islamic Social Finance for Sustainable Development and Planning of Village Assets: A Case ‎Study of Sumberdodol Village - Rahmawati, Yunaita; Amri , Muhtadin; Daroji , Choirul; Wahyuni , Ajeng; Rahayu, Eka (International Journal of Accounting and Economics Studies, 2025)
This research analyzes the role of a Sharia-compliant sustainability reporting model in increasing the effectiveness of Islamic social finance ‎for sustainable development and village asset management in Sumberdodol Village. The study employs a descriptive quantitative approach ‎, which integrates questionnaire surveys and structured interviews with the BUMDES management. The results showed that compliance with ‎Sharia law brings considerable improvements concerning a business’s financial management, accountability, and transparency. In particular, ‎the results observed improved transparency and accuracy in financial reporting, accountability in asset management, and a focus on social ‎responsibility coupled with strategic planning as core elements of financial management. The study concludes that the Sharia-compliant ‎sustainability reporting model successfully enhances Islamic social finance for sustainable development and village asset management in ‎rural areas while also offering pragmatic approaches to the management of village assets‎.